2011
DOI: 10.4236/ijg.2011.21005
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metals in Soils around the Cement Factory inRockfort, Kingston, Jamaica

Abstract: This study deals with the distribution of heavy metals in soils around one of the most important industries in Kingston, Jamaica i.e. the Carib Cement factory at Rockfort. The dust emitted from the Caribbean Cement Company Limited (Carib Cement), located in Rockfort, Kingston, gets deposited in course of time over the soil, leaves and forms a grey cover on the surrounding soils. Geochemical analysis of the top soil, collected from the present study area has been undertaken to assess the impact of the dust emit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 15 publications
3
11
0
Order By: Relevance
“…However, this is the first study performed in Brazil focused on estimating potential soil PTM contamination caused by cement plants operation and their potential health risks to local human population. Some studies have already been published relating concerning events of soil contamination by PTM and the anthropic activity of cement production in some regions of the world, reporting events of PTM soil contamination more severe than those observed in this study (Table 2), probably related to the fact that these previous studies have been performed in countries whose laws about gas emissions as well as soil contamination by PTM are less restrictive than in Brazil (El-Sherbiny et al 2019;Kolo et al 2018, Ogunkunle and Fatoba, 2014, Mandal and Voutchkov, 2011Al-Khashman and Shawabkeh, 2006). On the other hand, when considering studies on PTM contamination events in general, China is the country where most of these studies have been reported, indicating that soils from areas of intense urban and industrial activity are severely contaminated by PTM, creating alarming risks to the environment and the health of local populations (Han et al 2021, Ma et al 2020, Han et al 2020, Jin et al 2019, Yadav et al 2019.…”
Section: Resultsmentioning
confidence: 48%
See 1 more Smart Citation
“…However, this is the first study performed in Brazil focused on estimating potential soil PTM contamination caused by cement plants operation and their potential health risks to local human population. Some studies have already been published relating concerning events of soil contamination by PTM and the anthropic activity of cement production in some regions of the world, reporting events of PTM soil contamination more severe than those observed in this study (Table 2), probably related to the fact that these previous studies have been performed in countries whose laws about gas emissions as well as soil contamination by PTM are less restrictive than in Brazil (El-Sherbiny et al 2019;Kolo et al 2018, Ogunkunle and Fatoba, 2014, Mandal and Voutchkov, 2011Al-Khashman and Shawabkeh, 2006). On the other hand, when considering studies on PTM contamination events in general, China is the country where most of these studies have been reported, indicating that soils from areas of intense urban and industrial activity are severely contaminated by PTM, creating alarming risks to the environment and the health of local populations (Han et al 2021, Ma et al 2020, Han et al 2020, Jin et al 2019, Yadav et al 2019.…”
Section: Resultsmentioning
confidence: 48%
“…According to the U.S. environmental agency, 63 cement manufacturing plants are among the largest sources of hazardous pollutant emissions, including 64 PTM (Ogunkunle and Fatoba 2014, USEPA 2013, Yahaya et al 2013. Significant parts of these pollutants are deposited in the soil, including the burning of fuels for the kiln furnaces, generating fine dust particles that are deposited in the soil (Mandal and Voutchkov 2011). This dust contains PTM that are deposited in the soil and cause serious environmental and health impacts since it is not biodegraded, accumulating (Ogunkunle and Fatoba 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In some studies, higher concentrations of heavy metals in surface soils has been explained by limited mobility in soils having specifi c physical properties and alkaline reaction [19]. Other research has concluded that the human activity of cement production is the primary reason for nearby pollution by heavy metals [5,24]. However, it has been claimed that signifi cantly higher concentrations of heavy metals in the soil may not always be linked to cement factories [4].…”
Section: Discussionmentioning
confidence: 99%
“…Such compounds accumulate in surrounding land and aquifers, passing to the food chain (Travis et al. ; Al‐Khashman and Shawabkeh ; Mandal and Voutchkov ; Dong et al. ).…”
Section: Introductionmentioning
confidence: 99%